The influence of bureaucratic leadership style, work culture, and work discipline on the performance of employees of the Riau Islands Provincial secretariat with work motivation as an intervening variable - Sanjaya, Robi; Wibisono, Chablullah; Sajiyo, Sajiyo (Journal of Multidisciplinary Academic and Practice Studies, 2024)
Purpose: This study examines the influence of bureaucratic leadership style, work culture, and work discipline on employee performance at the Riau Islands Provincial Secretariat, with work motivation as an intervening variable. Research Methodology: Using a quantitative approach, 165 employees were selected as respondents from a population of 279 employees. Data were analyzed using structural equation Modelling (SEM) with AMOS 24.0. Results: The findings show that bureaucratic leadership style and work discipline significantly influence employee performance, whereas work culture has no significant direct effect. All three factors–leadership style, work culture, and discipline—positively and significantly affect motivation, which in turn strongly influences performance. Furthermore, motivation successfully mediated the relationships between leadership style, work culture, discipline, and employee performance, strengthening the overall causal model. Conclusions: Employee performance is primarily shaped by effective leadership, strong discipline, and supportive motivation, with work culture playing an indirect role. Motivation is a central driver that enhances the impact of leadership and discipline on performance outcomes. Limitations: This study is limited to a single public sector organization, with cross-sectional data that may not capture long-term dynamics. Future studies should incorporate other variables, such as teamwork, compensation, and organizational trust. Contribution: This study contributes to the public management literature by demonstrating the mediating role of motivation in linking bureaucratic leadership, culture, and discipline with performance, offering insights for policy and managerial practices in government institutions.